2017
DOI: 10.1158/1535-7163.mct-16-0613
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Nanoparticle–Mediated Delivery of Anti-miR-17 Family Oligonucleotide Suppresses Hepatocellular Carcinoma Growth

Abstract: Hepatocellular carcinoma (HCC) is one of the most common human malignancies with poor prognosis and urgent unmet medical need. Aberrant expression of multiple members of the miR-17 family are frequently observed in HCC, and their overexpression promotes tumorigenic properties of HCC cells. However, whether pharmacologic inhibition of the miR-17 family inhibits HCC growth remains unknown. In this study, we validated that the miR-17 family was upregulated in a subset of HCC tumors and cell lines and its inhibiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Anti-miR-17 therapy was examined in an autochthonous transgenic mouse model of MYC-driven HCC ( LAP-tTA/tet-O-MYC ) [ 17 ]. A lipid nanoparticle (LNP) encapsulating anti-miR-17 family oligonucleotide was utilized, as has been described previously (RL01-17(5))[ 15 ]. In LAP-tTA/tet-O-MYC transgenic mice MYC expression was induced at 4 weeks after birth leading to tumorigenesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anti-miR-17 therapy was examined in an autochthonous transgenic mouse model of MYC-driven HCC ( LAP-tTA/tet-O-MYC ) [ 17 ]. A lipid nanoparticle (LNP) encapsulating anti-miR-17 family oligonucleotide was utilized, as has been described previously (RL01-17(5))[ 15 ]. In LAP-tTA/tet-O-MYC transgenic mice MYC expression was induced at 4 weeks after birth leading to tumorigenesis.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that targeting miR-17 could be effective strategy for MYC driven cancers. Cell-line based studies have shown that targeting miR-17 can suppress tumor proliferation [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al delivered antimiR-17 with a lipid NP. MiR-17 is an oncogene, and ectopic expression with miR-17-3p results in the development of HCC in a mouse model [129,130]. The suppression of this oncogene through antimiR-17 delivery hindered the proliferation of HCC cells.…”
Section: Mirnasmentioning
confidence: 99%
“…15 Based on this work there has been a growing interest in developing anti-miR drugs designed to target the miR-17~92 cluster. [16][17][18][19][20][21] miR-17~92, however, is a complex polycistronic cluster that encodes 6 individual miRNAs (miR-17, miR-18a, miR-19a, miR-20a, miR-19b-1, and miR-92a-1). Moreover, the mammalian genome encodes two additional paralogous clusters known as miR-106a~363 and miR-106b~25.…”
Section: Introductionmentioning
confidence: 99%